2022
DOI: 10.3390/ma15207242
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance of Fly Ash Based Geopolymer (FAG) as Road Base Stabilizer

Abstract: This study examines the strength development of fly ash-based geopolymer (FAG) as a stabilizer for road base material for pavement construction. In the last decade, there has been a rapid development of conventionally treated bases, such as cement-treated bases. However, a major problem with this kind of application is the shrinkage cracking in cement-treated bases that may result in the reflection cracks on the asphalt pavement surface. This study explores the effects of FAG on base layer properties using mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…A comparison was made between FA-based geopolymer concrete and conventional concrete materials for the base layer [149]. The compressive strength ranged from 10.3 to 34.9 MPa for all geopolymer samples cured for 7, 28, and 90 days.…”
Section: Pavementmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison was made between FA-based geopolymer concrete and conventional concrete materials for the base layer [149]. The compressive strength ranged from 10.3 to 34.9 MPa for all geopolymer samples cured for 7, 28, and 90 days.…”
Section: Pavementmentioning
confidence: 99%
“…However, additional research on the behavior of geopolymer bases with the use of various raw materials is essential. In another study, Ojha and Lokesh [193] explored the possibility A comparison was made between FA-based geopolymer concrete and conventional concrete materials for the base layer [149]. The compressive strength ranged from 10.3 to 34.9 MPa for all geopolymer samples cured for 7, 28, and 90 days.…”
Section: Pavementmentioning
confidence: 99%
“…The presence of cracks in the base layer serves as a critical prerequisite for the emergence of reflective cracks. Scholars, through extensive research on semi-rigid base materials, have identified two primary factors contributing to the formation of shrinkage cracks [ 4 , 5 , 6 ]. The first factor involves stress induced by temperature fluctuations, while the second factor is stress resulting from the reduction in moisture content within the semi-rigid base material.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the desulfurization performance of the original magnesium slag is poor, a calcium conversion rate of up to 73.7% can be reached after mixing with additives or modification [34]. Magnesium slag, like other solid wastes, can also be used for mine filling [5,35,36] or road base material [37][38][39][40][41][42]. Numerous studies have conducted extensive research into other industrial solid wastes, such as granulated blast furnace slag [43][44][45], steel slag [46], red mud [47] and so on [48][49][50], which provide guidance for the utilization of the corresponding tailings and slag.…”
Section: Introductionmentioning
confidence: 99%